Low-loss organic ice micro-nano optical fiber and preparation method thereof
By dropping organic liquid between quartz fibers and using cooling materials and tensile technology to prepare organic ice micro-nano fibers, the problem of preparing high-quality organic ice micro-nano fibers in the prior art is solved, and low-loss and high-quality fiber preparation is achieved.
Patent Information
- Application Number
- CN202411694567.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-25
AI Technical Summary
It is difficult to prepare high-quality, low-loss organic ice micro-nano fibers with high quality, and especially in long lengths (for example >1 cm), crystalline optical fibers are prone to problems of high light scattering loss and propagation loss.
A preparation method is adopted to smoothly fill the gap by dropping the organic liquid to the gap between standard quartz single mode optical fibers, and to reduce the temperature to near the glass transition temperature of the organic liquid using cooling materials. Then, the quartz optical fiber is pulled at a constant speed to stretch the organic liquid to form a high-quality one-dimensional organic ice micro-nano fiber.
A high-quality organic ice micro-nano fiber with uniform diameter, smooth surface and low loss was achieved. The length can reach several centimeters, the transmission loss can be at least less than 0.03dB/cm, and it has good mechanical properties and stability.
Smart Images

Figure CN119575539A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of waveguide preparation, and in particular to a low-loss organic ice micro-nano optical fiber and a preparation method thereof. Background Art
[0002] Small organic molecules such as alkanes, alcohols and benzenes are widely present in the universe. Different from the common liquid and gaseous forms on Earth, in areas with more extreme conditions in the universe, many small organic molecules exist in solid form, which is called organic ice. For example, in the solar system, the average surface temperature of Mars is about -65°C, and as the distance from the sun increases, the average surface temperature of the planet will drop further. Since the optical properties of organic ice, such as infrared and ultraviolet spectra and polarization spectra, are extremely important for understanding the material environment of interstellar space and the evolution of celestial bodies, it is of great significance to explore its basic optical properties such as refractive index and absorption.
[0003] Micro-nano optical fiber refers to a one-dimensional optical waveguide with a diameter close to or smaller than the wavelength of the transmitted light. It has the advantages of low transmission loss, strong light field confinement, strong evanescent field, surface field enhancement, etc., and can be used to explore the extreme physical and chemical properties of materials. With the help of micro-nano optical fiber, a highly flexible and versatile research platform, making organic ice into a micro-nanoscale one-dimensional waveguide can promote organic ice research, deepen people's understanding of its mechanical and optical properties, and provide possibilities for organic ice-based technologies.
[0004] Micro-nano optical fibers can be divided into amorphous micro-nano optical fibers and crystalline micro-nano optical fibers, which have disordered and ordered structures respectively, show different optical and mechanical properties, and are suitable for different research and applications. Crystalline optical fibers have high light scattering loss and propagation loss due to the inevitable introduction of defects during their growth process. The growth rate of crystalline optical fibers is usually lower than the stretching rate of amorphous optical fibers. At longer lengths (e.g. >1cm), it is more difficult to obtain high quality for crystalline optical fibers. Summary of the invention
[0005] In order to solve the problems existing in the background technology, the present invention provides a low-loss organic ice micro-nano optical fiber and a preparation method thereof, which can better prepare high-quality one-dimensional organic ice micro-nano optical fiber with smooth surface, uniform diameter and low loss.
[0006] The organic ice micro-nano optical fiber prepared by the present invention provides a new platform for studying the physical and chemical properties of organic small molecules and expanding their applications as functional materials. It has great research and practical value in the fields of physical chemistry, materials science, life science and space exploration.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] 1. A method for preparing low-loss organic ice micro-nano optical fiber, the method comprising the following steps:
[0009] S1: two standard quartz single-mode optical fibers are placed at intervals along the same straight line, with a gap between the adjacent ends of the two standard quartz single-mode optical fibers as a sample preparation area, and an organic liquid is dripped into the gap between the quartz single-mode optical fibers to smoothly fill the gap, so that the adjacent ends of the two quartz optical fibers are finally connected by the organic liquid, that is, the dripped organic liquid is respectively connected to the end faces of the adjacent ends of the two quartz optical fibers;
[0010] S2: using a cooling material to lower the temperature of the sample preparation area to near the glass transition temperature of the added organic liquid, and slightly adjusting the temperature of the sample preparation area to be slightly higher than the glass transition temperature, so that the added organic liquid is in a highly viscous supercooled state;
[0011] S3: Pull the two standard quartz single-mode optical fibers at a uniform speed in opposite directions, thereby stretching the viscous organic liquid added until a uniform area of organic ice micro-nano optical fibers that meets the use length requirements is clearly seen, thereby obtaining high-quality one-dimensional organic ice micro-nano optical fibers, which still need to be kept at a low temperature during storage and use.
[0012] In the step S1, the size of the sample preparation area is several tens of micrometers to 100 micrometers.
[0013] In step S2, liquid nitrogen is used as the cooling material, and the sample preparation area is in a clean cold nitrogen atmosphere with adjustable temperature. The speed of reducing the temperature of the sample preparation area is greater than 50°C / s, and the temperature of the sample preparation area is slightly higher than the glass transition temperature of the organic liquid by about 0-15°C.
[0014] In step S3, the speed of uniformly pulling the standard quartz single-mode optical fiber is 0.05-1 mm / s.
[0015] Preferably, the proportion of the uniform area of the organic ice micro-nano optical fiber can be adjusted by adjusting the temperature of the sample preparation area and the speed of stretching the organic liquid.
[0016] In the step S1, the organic liquid is a glassy organic liquid or a binary mixed solution that can achieve glass transition.
[0017] The preparation method described in the present invention has been proven to be applicable to organic compound liquids such as methanol, ethanol, ethylene glycol, propylene glycol, glycerol, toluene, ethylbenzene, benzyl acetate, etc.; it is also applicable to organic binary mixed solutions, more specifically, organic binary mixed solutions mixed in a specified molar ratio such as chloroform-ethylbenzene (60:40), tetrachloromethane-ethylbenzene (50:50) and carbon disulfide-toluene (80:20), etc.
[0018] In step S3, the uniform area of the organic ice micro-nano optical fiber is a cylindrical area with uniform diameter in the middle of the two end cone areas formed after the organic liquid is stretched.
[0019] 2. Low-loss organic ice micro-nano optical fiber: The organic ice micro-nano optical fiber prepared by the preparation method has a uniform diameter and a smooth surface. The diameter can be from sub-wavelength to 10 μm, the length can reach several centimeters, and the root mean square roughness of the surface is less than 0.5 nm.
[0020] 3. An application of the organic ice micro-nano optical fiber in wave guiding, measurement of optical properties of organic small molecules and measurement of extreme mechanical properties.
[0021] 4. A method for detecting organic ice micro-nano optical fiber:
[0022] The method is:
[0023] Before or after the preparation of the organic ice micro-nano optical fiber is completed, the ends of two standard quartz single-mode optical fibers that are far away from each other are connected to the light source and the spectrometer respectively. The temperature of the sample preparation area is maintained below the glass transition temperature of the added organic liquid and above the liquid nitrogen temperature for waveguide measurement.
[0024] Preferably, the specific requirements for the temperature of the sample preparation area are determined by the test requirements. When performing single-wavelength waveguide measurement, one end of the quartz fiber is connected to a supercontinuum light source, with a wavelength bandwidth tunable filter (wavelength of about 400-800nm, single wavelength output, bandwidth of about 5-50nm adjustable), and the other side is connected to a spectrometer (wavelength 600-1700nm, resolution 0.05nm, maximum power +20dBm (100mW)). When performing wide-spectrum waveguide measurement, one end of the quartz fiber is connected to a high-brightness broadband light source (wavelength 190-2100nm, NA=0.22, 150mW), and the other side is connected to the same spectrometer as above. By analyzing the image of the microscope system and the data collected by the spectrometer, the detection results of the low-loss characteristics of the organic ice fiber are obtained.
[0025] The present invention has the following beneficial effects:
[0026] (1) The method of the present invention is the first to achieve the preparation of a variety of new small molecule organic micro-nano optical fibers with smooth surfaces and uniform diameters, and the root mean square roughness of the surface is less than 0.5 nm;
[0027] (2) The present invention can achieve precise control over a wide range of diameter and uniform zone length, wherein the diameter control can be achieved from sub-wavelength level to 10 μm, and the length can reach several centimeters;
[0028] (3) The method for preparing the organic ice micro-nano optical fiber of the present invention is applicable to a wide range of raw materials, and is applicable to a variety of organic liquids in a glassy state, and is also applicable to a variety of binary mixed solutions that can achieve glass transition;
[0029] (4) The two ends of the organic ice micro-nano optical fiber in the present invention are naturally connected to the quartz optical fiber, and the light field can be efficiently coupled into and out of the organic ice micro-nano optical fiber through the standard quartz optical fiber, realizing optical measurement and application;
[0030] (5) The organic ice micro-nano optical fiber prepared by the present invention can achieve low transmission loss in a wide band, with the minimum loss being less than 0.03 dB / cm;
[0031] (6) The organic ice micro-nano optical fiber prepared by the method of the present invention has good mechanical properties, low defect density and high structural uniformity, and thus has high toughness;
[0032] (7) Organic small molecules are ubiquitous in extraterrestrial planets or the universe, and have been proven to have good stability in these extreme environments (extremely low temperatures, cosmic radiation, etc.). Therefore, the optical fiber prepared directly using organic small molecules in the present invention is universal to the environment and can still maintain its ability to bend and stretch freely at temperatures below 100K.
[0033] (8) The organic ice micro-nano optical fiber prepared by the method of the present invention has a fast preparation speed, and it is easy to obtain a long and uniform structure. The stretching preparation speed is 0.05-1mm / s;
[0034] (9) The organic ice micro-nano optical fiber prepared in the present invention can realize active doping and low-threshold supercontinuum generation based on the advantages of organic materials such as dopability and high nonlinear coefficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is a schematic diagram of the device structure suitable for the method for preparing organic ice micro-nano optical fiber of the present invention.
[0036] Figure 2 This is an optical microscope photo of the ethanol ice optical fiber stretching process.
[0037] Figure 3 This is a schematic diagram of the device for waveguide measurement of organic ice micro-nano optical fiber.
[0038] Figure 4 This is a dark-field micrograph of laser light transmitted through an ethanol ice fiber.
[0039] Figure 5 This is a diagram of the broadband transmission characteristics of ethanol ice optical fibers with different diameters.
[0040] In the figure: 1. Microscope system, 2. Standard quartz single-mode optical fiber, 3. Electric translation stage, 4. Cold chamber, 5. Transparent viewing window, 6. Liquid nitrogen, 7. Lifting platform, 8. Temperature measuring line, 9. Pipette, 10. Organic liquid, 11. Optical fiber clamp, 12. Light source, 13. Spectrometer. DETAILED DESCRIPTION
[0041] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, but the present invention is not limited to the following embodiments.
[0042] Embodiments of the present invention are as follows:
[0043] Example 1
[0044] This embodiment assembles a preparation device suitable for the preparation method of the present invention. The structural schematic diagram of the preparation device is shown in FIG. Figure 1 As shown, the preparation device includes a microscope system 1, a standard quartz single-mode optical fiber 2, an electric translation stage 3, a cold chamber 4, a transparent visual window 5, a lifting platform 7, a thermocouple temperature measuring line 8 and an optical fiber clamp 11;
[0045] A transparent visual window 5 is installed on the top surface of the cold chamber 4, and two symmetrical through holes are opened on the transparent visual window 5. The microscope system 1 is installed directly above the transparent visual window 5 through an external support arm, and the lens of the microscope system 1 faces the transparent visual window 5. An electric displacement stage 3 is symmetrically arranged on both sides of the cold chamber 4, and a fiber clamp 11 is fixed on each electric displacement stage 3. Two standard quartz single-mode optical fibers 2 are fixed on the two fiber clamps 11 respectively by ultraviolet curing glue. The standard quartz single-mode optical fiber 2 passes through the through holes opened on the transparent visual window 5 together with the fiber clamp 11, and is movably inserted into the cold chamber 4. The two standard quartz single-mode optical fibers 2 in the cold chamber 4 are placed in parallel and arranged end to end.
[0046] The cold chamber 4 is placed on the lifting platform 7, and the cold chamber 4 contains a cooling material, and the cooling material is liquid nitrogen 6. In the initial state of the preparation device, an adjustable gap within tens of microns to 100 microns is provided between the ends of the two standard quartz single-mode optical fibers 2 in the cold chamber 4, which serves as a sample preparation area. The sample preparation area is placed within the field of view of the microscope system 1, and the microscope system 1 can observe and record the preparation process in the sample preparation area in real time through the transparent visual window 5. The probe of the thermocouple temperature measuring line 8 is suspended and close to the end face of the standard quartz single-mode optical fiber 2 to monitor the temperature near the sample preparation area in real time. By adjusting the height of the lifting platform 7, that is, adjusting the vertical distance between the liquid level of the liquid nitrogen 6 and the standard quartz single-mode optical fiber 2, the temperature of the sample preparation area can be changed or maintained for a long time.
[0047] The preparation device further comprises a pipette 9 for extending into the cold chamber 4 to drip an organic liquid 10 .
[0048] The method for preparing organic ice micro-nano optical fiber using the preparation device comprises the following steps:
[0049] (1) First, adjust the height of the lifting platform 7 to the lowest, remove the cold chamber 4, glue a standard quartz single-mode optical fiber 2 on each optical fiber clamp 11, and place the proximal end areas of the two standard quartz single-mode optical fibers 2 along the same straight line at intervals, with a gap between the adjacent ends of the two standard quartz single-mode optical fibers 2 as a sample preparation area, add liquid nitrogen 6 whose liquid level is lower than that of the standard quartz single-mode optical fibers 2 into the cold chamber 4, and then put the cold chamber 4 back on the lifting platform 7. At this time, the environment near the standard quartz single-mode optical fibers 2 is at room temperature, and the part inside the cold chamber 4 is in a clean cold nitrogen atmosphere with adjustable temperature;
[0050] (2) A small amount of organic liquid is sucked by the pipette 9, and then the pipette 9 is extended into the cold chamber 4, and a drop of organic liquid 10 is dripped into the sample preparation area, and the sample preparation area is smoothly filled by the surface tension of the organic liquid 10;
[0051] (3) By raising the height of the lifting platform 7 to drive the cold chamber 4, the vertical distance between the liquid nitrogen 6 and the standard quartz single-mode optical fiber 2 is adjusted, thereby lowering the temperature of the sample preparation area to near the glass transition temperature of the added organic liquid, and fine-tuning the temperature of the sample preparation area to be slightly higher than the glass transition temperature, so that the added organic liquid is in a highly viscous supercooled state;
[0052] (4) The standard quartz single-mode optical fiber 2 is moved in the opposite direction at a uniform speed by the electric translation stage 3, thereby stretching the added organic liquid 10 until a uniform region of organic ice micro-nano optical fiber that meets the use length requirement is clearly present, thereby obtaining the organic ice micro-nano optical fiber.
[0053] Example 2
[0054] This embodiment provides a specific implementation process of preparing ethanol ice optical fiber using the preparation method of the present invention. The stretching process of ethanol ice optical fiber near -175℃ is as follows Figure 2 As shown, during the stretching process, as the stretching length increases, the diameter of the ethanol ice fiber gradually decreases. The connection between the ethanol ice fiber and the quartz fiber is a conical area with a drastic change in diameter, and the middle is a uniform diameter area. The stretching speed of ethanol shown in the figure is 0.3mm / s.
[0055] Example 3
[0056] This embodiment provides a specific implementation process for quality inspection of the organic ice micro-nano optical fiber obtained by the preparation method of the present invention. In order to characterize its light field transmission characteristics such as loss, a light source 12 and a spectrometer 13 can be connected to the outer ends of two standard quartz single-mode optical fibers before or after the preparation of the organic ice micro-nano optical fiber to perform waveguide measurement. The schematic diagram of the device for waveguide measurement is shown in FIG. Figure 3As shown, the light field is efficiently coupled into the organic ice fiber through the left quartz fiber, and then collected by the right quartz fiber into the spectrometer 13. By analyzing the image of the microscope system 1 and the data collected by the spectrometer 13, the low loss characteristics of the organic ice fiber can be detected.
[0057] Microscope system test results are as follows Figure 4 As shown, Figure 4 These are dark field micrographs of the ethanol ice fiber transmitting 475nm, 500nm, 525nm, 550nm, 575nm, and 600nm lasers. It can be seen from the dark field micrographs that there is no obvious scattering on the surface of the organic ice fiber, but only at the output end, that is, the coupling region where the light enters the quartz fiber from the organic ice fiber, there is strong scattering. At the input end, that is, the coupling region where the light enters the organic ice fiber from the quartz fiber, the light field scattering is weak, which indicates that the light field can efficiently enter the organic ice fiber.
[0058] The spectrometer test results are as follows Figure 5 As shown, Figure 5 The broadband transmission characteristics of ethanol ice fibers with different diameters are shown. The wavelength range of broadband light is 400-1550nm. Due to the cutoff of high-order modes, as the diameter of organic ice fibers decreases, the transmission power tends to decrease.
[0059] The above specific implementation modes are used to explain the present invention rather than to limit the present invention. Any modification and change made to the present invention within the spirit of the present invention and the protection scope of the claims shall fall within the protection scope of the present invention.
[0060] The above description is only a preferred embodiment of the present invention, so all equivalent changes or modifications made according to the structure, characteristics and principles described in the scope of the patent application of the present invention are included in the scope of the patent application of the present invention.
Claims
1. A method for preparing low-loss organic ice micro-nano optical fiber, characterized in that: The method comprises the following steps: S1: Place two quartz single-mode optical fibers at intervals along the same straight line, with a gap between the two adjacent ends of the two quartz single-mode optical fibers as a sample preparation area, and drop an organic liquid into the gap between the quartz single-mode optical fibers to smoothly fill the gap; S2: using a cooling material to lower the temperature of the sample preparation area to near the glass transition temperature of the added organic liquid, and adjusting the temperature of the sample preparation area to be higher than the glass transition temperature; S3: The two quartz single-mode optical fibers are pulled at a uniform speed in opposite directions, thereby stretching the added organic liquid until a uniform region of organic ice micro-nano optical fibers that meets the use length requirements appears, thereby obtaining organic ice micro-nano optical fibers.
2. The method for preparing a low-loss organic ice micro-nano optical fiber according to claim 1, characterized in that: In the step S1, the size of the sample preparation area is several tens of micrometers to 100 micrometers.
3. The method for preparing a low-loss organic ice micro-nano optical fiber according to claim 1, characterized in that: In the step S2, liquid nitrogen is used as the cooling material, the speed of reducing the temperature of the sample preparation area is greater than 50°C / s, and the temperature of the sample preparation area is 0-15°C higher than the glass transition temperature of the organic liquid.
4. The method for preparing a low-loss organic ice micro-nano optical fiber according to claim 1, characterized in that: In the step S3, the speed of uniformly pulling the quartz single-mode optical fiber is 0.05-1 mm / s.
5. The method for preparing a low-loss organic ice micro-nano optical fiber according to claim 1, characterized in that: In the step S1, the organic liquid is a glassy organic liquid or a binary mixed solution that can achieve glass transition.
6. The method for preparing a low-loss organic ice micro-nano optical fiber according to claim 1, characterized in that: In step S3, the uniform area of the organic ice micro-nano optical fiber is a cylindrical area with uniform diameter in the middle of the two end cone areas formed after the organic liquid is stretched.
7. A low-loss organic ice micro-nano optical fiber, characterized by: The preparation method is described in any one of claims 1 to 6.
8. Application of the organic ice micro-nano optical fiber made by the preparation method described in any one of claims 1 to 6 in wave guiding, measurement of optical properties of organic small molecules and measurement of ultimate mechanical properties.
9. A method for detecting organic ice micro-nano optical fiber prepared by the preparation method described in any one of claims 1 to 6.
10. The detection method according to claim 9, characterized in that: The method is: before or after the preparation of organic ice micro-nano optical fiber is completed, the ends of two quartz single-mode optical fibers that are far away from each other are respectively connected to a light source and a spectrometer, and the temperature of the sample preparation area is maintained below the glass transition temperature of the added organic liquid and above the liquid nitrogen temperature to perform guided wave measurement.
Citation Information
Patent Citations
Ice micro-nano optical fiber capable of being used for wide-spectrum low-loss optical guided waves
CN113433616A
Flexible micro-nano optical fiber coupler, micro strain sensing application system and preparation method
CN115308842A
Ice microsphere optical resonant cavity, preparation device and preparation method
CN117394124A
Method and device for manufacturing optical transmission body
JP2003329857A
Frozen-fluid fiber guide
US20040146262A1